2 A "direct" transfer protocol for patients with non ST-elevation myocardial infarction reduces time to coronary angiography. (9th June 2011) - Gallagher, S M; Lovell, M J; Jones, D; Ferguson, E; Antoniou, S; Mohiddin, S; Westwood, M; Mathur, A; Archbold, R A; Knight, C; Jain, A K
Abstract : Introduction: Patients with non-ST elevation myocardial infarctions (NSTEMI) are at high risk of further cardiac events. National guidelines recommend "early" coronary angiography within 96 h of presentation. Most patients with NSTEMI present to their district general hospital (DGH), and await transfer to the regional cardiac centre for angiography. This care model has inherent time delays, and delivery of early angiography is problematic. Methods: A novel clinical care pathway for the management of NSTEMI, known locally as the Heart Attack Centre-Extension or HAC-X, has been investigated. This pathway identifies patients with NSTEMI by clinical assessment and rapid point-of-care troponin testing while in the emergency department (ED). Patients meeting criteria for urgent transfer receive evidence based medical therapy for NSTEMI (see Abstract 2 table 1 ) in the ED, and are transferred to the tertiary centre within 1 h without referral. All unstable patients are taken straight to the cardiac catheterisation laboratory. For stable patients, coronary angiography is undertaken on the same day, or if patients arrive after 17:00 on the next available routine list. The study group consists of 775 patients divided into two groups; 464 patients treated before the instigation of the HAC-X pathway (Pre-HACX), and 311 patients treated via the novel pathway (Post-HACX). We have undertaken a prospective observational study of post-HAC-X patients, assessing need for angiography and or revascularisation along with discharge diagnosis. We have also compared the waiting time for angiography of pre-HAC-X and post-HAC-X groups. Results: 250/311 (80.4%) of HACX patients underwent angiography. Following angiography, 144/250 (57.6%) were treated with coronary revascularisation (108 (75%) PCI and 36 (25%) CABG). 106/250 (42.4%) of patients were treated with medical therapy alone. NSTE-ACS (encompassing NSTEMI and unstable angina) was the discharge diagnosis for 75.4% of HACX patients. 10% of patients had another cause for chest pain symptoms (including pericarditis and, myocarditis); 14.6% had a non-cardiac diagnosis. Mean time from presentation to angiography was pre-HAC-X 7349 mins (±6836) and post HAC-X 754 mins (±458) (p<0.0001) (see Abstract figure 1 ). Pre-HAC-X mean wait for transfer to tertiary centre was 4.1 (±4.7) days. Median length of stay for HACX patients was 3 days. HAC-X has reduced wait for coronary angiography by 3.4 days per patient. Conclusions: This novel care pathway allows delivery of early angiography to NSTEMI patients in accordance with national guidance. Importantly, the pathway allows accurate diagnosis of NSTEMI, and inappropriate transfers are infrequent. Its introduction has resulted in a significant reduction in time to angiography for NSTEMI patients, and significant reductions in total hospital bed occupancy for patients with NSTEMI.